Reduced humidity experienced by mice in vivo coincides with reduced outflow facility measured ex vivo. (September 2019) - Reina-Torres, Ester; Bertrand, Jacques A.; O'Callaghan, Jeffrey; Sherwood, Joseph M.; Humphries, Peter; Overby, Darryl R.
Abstract: Mice are routinely used to study aqueous humour dynamics. However, physical factors such as temperature and hydration affect outflow facility in enucleated eyes. This retrospective study examined whether differences in temperature and relative humidity experienced by living mice within their housing environment in vivo coincide with differences in outflow facility measured ex vivo . Facility data and environmental records were collected for one enucleated eye from 116 mice (C57BL/6J males, 9–15 weeks old) at two institutions. Outflow facility was reduced when relative humidity was below the lower limit of 45% recommended by the UK Code of Practice, but there was no detectable effect of temperature on outflow facility. Even when accounting for effects of humidity, there were differences in outflow facility measured between institutions and between individual researchers at the same institution. These data indicate that humidity, as well as additional environmental factors experienced by living mice within their housing environment, may significantly affect outflow facility measured ex vivo . Highlights: The relative humidity experienced by living mice affects outflow facility measured after death. A relative humidity below approximately 45% corresponds to a nearly 30% reduction in outflow facility . Outflow facility was significantly different between institutions and between researchers despite similar relative humidity. Humidity and environmental conditions in the housing environment should be controlled when measuring outflow facility in mice.